Trends in the availability and prices of quality-assured tuberculosis drugs: a systematic analysis of Global Drug Facility Product Catalogs from 2001 to 2024 - Kohler, Stefan; Achar, Jay; Mulder, Christiaan; Sitali, Norman; Paul, Nicolas (Globalization and health, 2024)
BACKGROUND: The Global Drug Facility (GDF) of the Stop TB Partnership was launched in 2001 with the goal of increasing access to quality-assured tuberculosis (TB) drugs and products. We aimed to describe the TB drugs and prices available from the GDF over time and to assess trends. - METHODS: We searched the internet, including an internet archive, for past and recent GDF Product Catalogs and extracted the listed TB drugs and prices. We calculated the lowest price for the most common drug formulations assuming drugs with similar active pharmaceutical ingredients (APIs) are substitutes for each other. We assessed time trends in the TB drugs and prices offered by the GDF in univariable regressions over the longest possible period. - RESULTS: We identified 43 different GDF Product Catalogs published between November 2001 and May 2024. These product catalogs included 122 single medicines (31 APIs), 28 fixed-dose combinations (9 API combinations), and 8 patient kits (8 API regimens and other materials). The number of TB drugs listed in the GDF Product Catalog increased from 9 (8 APIs) to 55 (32 APIs). The price decreased for 17, increased for 19, and showed no trend for 12 APIs. The price of 15 (53.6%) of 28 APIs used against drug-resistant TB decreased, including the price of drugs used in new treatment regimens. The decreasing price trend was strongest for linezolid (-16.60 [95% CI: -26.35 to -6.85] percentage points [pp] per year), bedaquiline (-12.61 [95% CI: -18.00 to -7.22] pp per year), cycloserine (-11.20 [95% CI: -17.40 to -4.99] pp per year), pretomanid (-10.47 [95% CI: -15.06 to -5.89] pp per year), and rifapentine (-10.46 [95% CI: -12.86 to -8.06] pp per year). The prices of 16 (61.5%) of 23 APIs for standard drug-susceptible TB treatment increased, including rifampicin (23.70 [95% CI: 18.48 to 28.92] pp per year), isoniazid (20.95 [95% CI: 18.96 to 22.95] pp per year), ethambutol (9.85 [95% CI: 8.83 to 10.88] pp per year), and fixed-dose combinations thereof. - CONCLUSIONS: The number of TB drugs available from the GDF has substantially increased during its first 23 years of operation. The prices of most APIs for new TB treatments decreased or remained stable. The prices of most APIs for standard drug-sensitive TB treatment increased.
Gesehen am 13.02.2025